Economic valuation of the thermal inertization of asbestos waste—an Italian case study - Silvia Ferrini; Filippo Pampaloni; Francesco Delogu; Giulia Goffetti; Cecilia Viti; Giancarlo Capitani (Academia Environmental Sciences and Sustainability)
Asbestos-containing waste presents a multifaceted challenge to governments and society, demanding innovative solutions. This article unveils options to manage asbestos-containing waste and analyze merits and drawbacks of thermal inertization technology, focusing on a newer patent which reduces the treatment time (and costs) and yields a reusable, asbestos-neutral building material. Impact assessment requires the formal valuation of a new project, technology, or program. In this article, we present a mixed-method approach (life cycle analysis with an extended cost–benefit analysis) and provide insights into the financial, economic, and environmental dimensions of asbestos-containing waste. The results suggest that inertization technologies hold the promise of a sustainable alternative to deep landfill burial. However, their success is contingent on securing public funding, a thorough examination of hidden environmental costs and risks, and the establishment of supportive regulations fostering a circular economy. These findings underscore the imperative for further exploration and substantial financial commitments to make asbestos treatment options a global reality.